Modeling and Simulation of Superconducting Magnetic Energy Storage Systems - Ashwin Kumar Sahoo; Nalinikanta Mohanty; Anupriya M (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper aims to model the Superconducting Magnetic Energy Storage System (SMES) using various Power Conditioning Systems (PCS) such as, Thyristor based PCS (Six-pulse converter and Twelve-pulse converter) and Voltage Source Converter (VSC) based PCS. Modeling and Simulation of Thyristor based PCS and VSC based PCS has been carried out. Comparison has also been carried out based on various criteria such as Total Harmonic Distortion (THD), active and reactive power control ability, control structure and power handling capacity. MATLAB/Simulink is used to simulate the various Power Conditioning Systems of SMES.